Peran Pembangunan Proyek Smelter Manyar dalam Meningkatkan Pendapatan Masyarakat Ditinjau dari Manajemen Syariah - Masrur, Muhammad (BISMA : Business and Management Journal, 2024)
This research aims to determine the role of the development of the Manyar Smelter project and its influence in increasing community income in terms of sharia management. The method used is qualitative obtained from primary and secondary data. The results of this research show that the economic condition of the community before the construction of the Manyar Smelter project was sufficient to meet prosperity. The role of the construction of the Manyar Smelter project in increasing people's income has a huge impact on the community's economy. Apart from recruiting local workers, it also has an impact on the MSME aspect of the surrounding community. So that the level of welfare is more than adequate. Of course, this increase must also be accompanied by financial management in accordance with Islamic financial principles